A REVISION OF THE MALAYSIAN NELSONIEAE (SCROPHULARIACEAE) - Bremekamp, C. E. B. (Research Center for Biology, 1955)
This revision of the Malaysian genera of Nelsonieae,of which an emended description is given, covers three genera, Staurogyne Wall.(52 species),Nelsonia R. Br.(1),and Elytraria Vahl (2).A new subdivision of Staurogyne is proposed.Among the new taxa described are 24 species (including 1 variety raised to specific rank) and 18 varieties. Moreover,4 new combinations and 1 new name are proposed.